Colonic mass movements in idiopathic chronic constipation. Issue 9 (September 1988) - Bassotti, G; Gaburri, M; Imbimbo, B P; Rossi, L; Farroni, F; Pelli, M A; Morelli, A
Abstract : As relatively little is known of human colonic motor activity either in health, or in pathological conditions, we investigated mass movements in 14 chronically constipated patients and 18 healthy volunteers. Mass movements were recorded from proximal and distal colon during 24 h (12 noon-12 noon) by a colonoscopically positioned multilumen manometric probe and low compliance infusion system. Patients and controls differed significantly in the number (mean 2.6 (0.7) v 6.1 (0.9) (SE), p = 0.02) and duration (mean 8.2 (1.6) v 14.1 (0.8) s, p = 0.04) of mass movements. The data suggest that one pathophysiological mechanism of constipation may be decreased propulsive activity. A circadian pattern, with a significant difference between day and night distribution, was documented in both groups. The patients reported decreased defecatory stimulus concomitant with the mass movements.